2021
DOI: 10.3390/su13095276
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Prediction of Eight Potentially Toxic Elements by Pistia stratiotes L. Grown in the Al-Sero Drain (South Nile Delta, Egypt): A Biomonitoring Approach

Abstract: The potential to utilise the free-floating macrophyte Pistia stratiotes L. to survey contamination of the Al-Sero Drain in the South Nile Delta, Egypt, by eight potentially toxic elements (PTEs) was investigated in this study. This study considered the absorption of eight PTEs (Cd, Co, Cu, Fe, Mn, Ni, Pb, and Zn), and the evaluated P. stratiotes were located in three sampling locations along the Al-Sero Drain, with sampling conducted in both monospecific and homogenous P. stratiotes. Samples of both types of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The biomass of P. stratiotes can be utilized to produce fertilizers and compost, and the utility of P. stratiotes as an organic phosphate fertilizer for rice cultivation has also been investigated (Polthanee et al, 2015). The potential of P. stratiotes biomass as an organic fertilizer for tomato cultivation has also been reported (Eid et al, 2021). Studies have shown the effectiveness of using macrophytes as organic fertilizers because they accumulate high concentrations of nutrients present in the water (Martínez-Soto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The biomass of P. stratiotes can be utilized to produce fertilizers and compost, and the utility of P. stratiotes as an organic phosphate fertilizer for rice cultivation has also been investigated (Polthanee et al, 2015). The potential of P. stratiotes biomass as an organic fertilizer for tomato cultivation has also been reported (Eid et al, 2021). Studies have shown the effectiveness of using macrophytes as organic fertilizers because they accumulate high concentrations of nutrients present in the water (Martínez-Soto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the biomass shows increasing carbon absorption, which is attributed to the ability of P. stratiotes and S. molesta to utilize organic and inorganic contaminants as energy and carbon sources (Kumar et al 2017). The increase in biomass with after treatment of landfi ll leachates also shows the infl uence of the landfi ll leachate and CW sediment nutrient status on the rate of decomposition and respiration rate in P. stratiotes and S. molesta (Eid et al 2021). This is because factors such as sediment quality, water chemistry, nutrient inputs, and interspecifi c competition play a role in the growth and establishment of macrophytes (Clarke and Wharton 2001).…”
Section: Biomass and Bioaccumulation Factor Of P Stratiotes And S Mol...mentioning
confidence: 95%